Mihrabs in the middle Maghreb in the middle ages - boukazoula, abdelmalek (Journal of Social Sciences and Humanities, 2021)
Muslim civilization has known a high degree of development and progress in many fields especially in the Islamic architecture. Generally, architecture had a function elements that concern solidity and art. The architecture ; wether religious, civil or military completes its role without forgetting the beauty side. Solidity and beauty were bothe taken into consideration particularly in mosques that contain Mihrabs (corner where the Imam stands up). In fact, the Mihrab had a great spiritual value for Mulims because it is the main place in the prayer houses.